PS-B01-12: SEXUAL DIMORPHISM OF CEREBROVASCULAR NOX5-NOTCH3 SIGNALLING IN ANGIOTENSIN II-INDUCED HYPERTENSION. (January 2023) - Blaikie, Zachariel S L; Montezano, Augusto C; Miller, Alyson A; Touyz, Rhian M; Work, Lorraine M
Abstract : Objectives: NOX5 is a pro-contractile NOX isoform associated with vascular dysfunction. We demonstrated that vascular NOX5 expression is increased in cerebral autosomal dominant arteriopathy with sub-cortical infarcts and leukoencephalopathy (CADASIL), a small vessel disease of the brain. CADASIL is caused by mutations in NOTCH3 and abnormal NOTCH3 signalling. Here we questioned whether cerebrovascular NOX5 influences NOTCH3 in male and female hypertensive mice. Design and method: Brain tissues from angiotensin II (Ang II) male and female 20-week wild-type (WT) ice and mice expressing human Nox5 (hNOX5) specifically in VSMCs studied. Ang II was administered by mini-pump (600ng/Kg/per day) for 28 days to induce a hypertension. Protein and mRNA expression of NOX isoforms and NOTCH3 (full-length and intracellular domain (ICD)) and downstream signalling of NOTCH3-specific genes were assessed using qPCR and immunoblotting respectively. Markers of oxidative stress were measured by Amplex-red and TBARS-MDA. Results: Ang II induced a significant increase in blood pressure in WT and hNOX5 mice. Expression of full length NOTCH3 expression was significantly increased in male Ang II-treated hNOX5 mice (AU: 0.15 ± 0.01 vs. un-treated hNOX5 0.07 ± 0.02) and unchanged in females. NOTCH3-ICD was significantly increased in male Ang II-treated WT versus WT controls (0.1 ± 0.01 untreated WT vs. 0.25 ± 0.05 Ang II WT), but unchanged in male hNOX5 mice. NOTCH3-ICD expression was unaltered in female untreated versus Ang II treated WT and hNOX5 mice. Downstream NOTCH3 gene HEY1 mRNA expression was significantly reduced in male Ang II-treated hNOX5 mice compared to untreated hNOX5 males (3.91 ± 0.3 vs. male hNOX5 untreated 2.78 ± 0.13). Irreversible protein tyrosine phosphatases (PTP-ox) were significantly increased in Ang II-treated hNOX5 mice (AU: 4.91 ± 0.6 vs. 2.18 ± 0.14) and was unchanged in hNOX5 female mice. MDA lipid peroxidation markers were decreased in female hNOX5 Ang II-treated mice (umol/protein: 1.28 ± 0.26 vs. hNOX5 3.25 ± 0.43), but not males. NOX5 induced no changes in NOX1-4 protein expression, or ROS measures in males or females. Conclusions: Ang II-induced hypertension in VSMC-specific NOX5 mice leads abnormal NOTCH3 signalling, downstream HEY1 transcription, and increased PTP-ox in a sex-dependent manner. In conclusion, in brains from VSMC-specific hNOX5 mice under a hypertensive phenotype, NOTCH3 expression is increased with associated attenuation of NOTCH3 downstream gene expression and increased PTP signalling. These findings were only evident in male mice. Our data suggest a possible relationship between NOTCH3 signalling and NOX5 that seems to be sex-specific. Implications of this sexual dimorphism await further clarification in the context of hypertension and vascular dysfunction.